Analisis Konseptual Model Pembelajaran PAI Berbasis Deep Learning Dalam Mengonstruksi Pemahaman Religius Siswa - Hasan Nurdin (PT. Pusmedia Group Indonesia, 2026)
This study uses a library research approach. This study is motivated by the still low religious understanding of students in Islamic Religious Education (PAI) learning which tends to be textual and memorization-oriented. This condition indicates the need for a learning approach that is able to encourage deep and meaningful understanding. This study aims to analyze the concept of a PAI learning model based on deep learning, examine the process of reflection and appreciation of values, and identify the role of the model in the internalization of religious values of students. The methodology used is library research by reviewing various scientific literature in the form of relevant books and journals. Data analysis techniques are carried out descriptively-analytical through the process of reduction, classification, and synthesis of concepts. The results of the synthesis show that the PAI learning model based on deep learning is able to increase the understanding of the meaning of Islamic teachings in depth, encourage reflection and appreciation of values personally, and strengthen the internalization of religious values in cognitive, affective, and psychomotor aspects. Thus, this approach is effective in forming students' religious character holistically and contextually.